Perkembangan Masyarakat Berbasis Multikultural Dimensi Horizontal - zainal arifin; Luluk Indarinul Mufidah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
This study is to analyze how the development of Indonesian society is based onmulticultural horizontal dimensions. The development of a multicultural-based societycan be said to be a change from the social symptoms that exist in a multicultural society,where these communities can live side by side peacefully (peaceful coexistence) incultural differences. The characteristics of a multicultural based society are as follows:(1); The occurrence of segmentation in the form of groups that often have sub-culturesthat are different from one another (2); Has a social structure divided into noncomplementaryinstitutions (3); Lack of developing consensus among its members onbasic values (4); Relatively, they often experience conflicts between one group andanother (5); Relatively, social integration grows on coercion and dependence in theeconomic field and (6), there is political domination by one group over other groups. Thedevelopment of a multicultural based society with horizontal dimensions in Indonesia isat; (a) Nationtribes plurality, (b) Religious plurality: (1) Hindu-Buddhist influence, (2)Islamic Cultural Influence, (3) Western Cultural Influence, (c) GeographicalEnvironment Influence